USK FKIP PPKn STUDENTS PERCEPTIONS OF CONTENT ON TIKTOK SOCIAL MEDIA - tajul ghina; Ruslan; Ridayani (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research investigates the types of content commonly used by PPKn students on TikTok and the perceptions of Syiah Kuala University students, particularly in the Pancasila and Citizenship Education program, regarding TikTok content. The study aims to explore the content preferences of PPKn students and their views on TikTok. TikTok is a digital platform where users can share videos and interact via comments, private chats, and live broadcasts. Using a qualitative, descriptive approach, the study involved 13 active PPKn students from FKIP USK (2021-2023). Data were collected through direct interviews. The discovery of this research is: 1) Students understand social media’s purpose in providing learning resources and viral news, with both positive impacts (staying informed) and negative impacts (social media addiction). 2) PPKn students primarily use TikTok for entertainment and educational purposes, such as finding tutorials on creating automatic tables of contents and bibliographies and searching for web journals.